Rough colloids at fluid interfaces: from fundamental science to applications - Rahman, Md Anisur; Beltramo, Peter J. (Frontiers in Physics, 2023)
Colloidal particles pinned to fluid interfaces have applications ranging from Pickering emulsions and foams to the development of 2D materials via Langmuir-Blodgett deposition. While colloids come in virtually any size, shape, and chemistry, particle surface topography, or roughness, has recently found renewed interest as a design parameter for controlling interfacial pinning, capillary interactions, assembly, and mechanics of particulate monolayers. In this review, we highlight the fundamental science regarding rough colloidal particles at fluid interfaces and how manipulating roughness can be a tool for material design, rather than merely a characteristic needing to be dealt with. While existing work reveals the importance of roughness, the field is still rather nascent and therefore this review highlights both challenges and opportunities for future research.